Assessment of the pesticides atrazine, endosulfan sulphate and chlorpyrifos for juvenoid-related endocrine activity using Daphnia magna - Palma, Patrícia (2013)
The water flea Daphnia magna belongs to the cyclical parthenogenic species, which can reproduce by either parthenogenesis or sexual reproduction. Recent studies have reported the involvement of the methylfarnesoate hormone, in male sex determination of D. magna. The aim of this study was to evaluate the juvenoid and anti-juvenoid activity of atrazine, endosulfan sulphate, and chlorpyrifos. To assess the juvenoid activity we exposed maternal daphnids to several concentrations of the respective pesticides, using the percentage of male production as endpoint. Fenoxycarb (1 μg L−1) was used as a positive control. The anti-juvenoid activity was assessed using a similar bioassay after the addition of fenoxycarb (1 μg L−1) to all test solutions. Fenoxycarb is an insect growth regulator that mimics the action of methylfarnesoate, and promoted the production of 95% of male offspring at the given concentration. Weak juvenoid-agonist activity was detected for endosulfan sulphate, with a significant increase of the percentage of male daphnids detected through logistic regression. In addition, atrazine and endosulfan sulphate antagonized the juvenoid activity of fenoxycarb. These results also corroborate the hypothesis that weak juvenoid agonists can simultaneously act as juvenoid antagonists as it has been observed in other hormonal systems.